A dynamic message-passing approach for social contagion in time-varying multiplex networks. (24th October 2018) - Su, Zhen; Kurths, Jürgen
Abstract: The information about social behavior diffusion on a communication network and the social behavior contagion through a physical-contact network are two related dynamical processes. We investigate here an asymmetrically interacting, double-layer network to elucidate the interplay between information diffusion on a time-varying network and the social contagion on the counterpart layer. We uncover that the time-varying character affects the final adoption size. We also find that the behavior spreading in the physical-contact network introduces the adoption size from first to second order. A maximizing area of the difference between the final infected size and the adoption size appears in a suitable range of the behavioral information transmission rate and the initial seed size. We develop a dynamic message-passing theory to understand the interplay between both types of spreading dynamics.